2010
DOI: 10.1097/brs.0b013e3181ae561d
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Nerve Endings in Iliolumbar Ligament

Abstract: Immunohistochemical staining has shown that iliolumbar ligament had a rich nerve tissue. Those results indicate that ILL plays an important role in proprioceptive coordination of lumbosacral region alongside its known biomechanic support function. Moreover, the presence of type IV nerve endings suggest that the injury of this ligament might contribute to the low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Yahia et al. (1992) reported the presence of both Ruffini and Pacini endings in the supraspinous and interspinous ligaments, and a recent examination of the iliolumbar ligament found this tissue to be abundantly innervated by Pacinian receptors and Ruffini endings as well as a few Golgi tendon organs (Kiter et al. 2010).…”
Section: Innervation Of the Tlfmentioning
confidence: 99%
“…Yahia et al. (1992) reported the presence of both Ruffini and Pacini endings in the supraspinous and interspinous ligaments, and a recent examination of the iliolumbar ligament found this tissue to be abundantly innervated by Pacinian receptors and Ruffini endings as well as a few Golgi tendon organs (Kiter et al. 2010).…”
Section: Innervation Of the Tlfmentioning
confidence: 99%
“…44,45 Furthermore, the author now knows the ligaments of the SIJ have a more complex neural structure, 1,46 which provide not only a potential as well as a pain generator but also likely important proprioceptive feedback. [47][48][49] Thus, the author could argue that the ligamentous structure of the SIJ not only contribute to form closure or passive stability but are also likely involved in the dynamic stability of the pelvic ring. The term 'force closure' was coined by Vleeming et al 11 and used to describe the compression forces acting on the SIJ related to dynamic stability of the joints.…”
Section: Mechanical Stability Of the Sijmentioning
confidence: 99%
“…Moreover, recent research has found nociceptors to be present throughout the joint capsule, ligaments and potentially into the subchondral bone, which suggests that trauma to any of the surrounding structures may be an aetiology of posterior pelvic or low back pain. 3,47,84 There are two mechanical mechanisms described in the literature that drive posterior pelvic pain in failed load transfer. The primary driver for both mechanisms is failed force closure, one is related to altered motor control (Right side of model; Fig.…”
Section: Motor Control and Lumbar -Pelvic Stabilitymentioning
confidence: 99%
“…These include Homo erectus [87], Homo heidelbergensis [88], ancient Egyptians and Nubians [89], ancient Chinese populations [90] and Ötzi the Iceman [91]. This included disc herniation, spondylolisthesis, scoliosis, osteophytosis, rheumatoid arthritis, osteoarthritis, lumbar spur formation, and ankylosing spondylitis all of which have the potential to cause LBP [1,[20][21][22][23][24][25][26][27][28][29][30]. So in consideration of Anderson's [58] invocation of dual level control in determining LBP in humans it would seem that the cultural environment, despite varying considerably between populations, has little impact upon LBP prevalence.…”
Section: Lbp In Traditional Indigenous Populationsmentioning
confidence: 99%
“…Abnormality or injury in several structures in the lumbar spine, including the facet joints [22,23], intervertebral discs [24,25], and ligamentous tissues [26] are prevalent in LBP and can contribute to pain. In fact any of the anatomical structures of the spine may contribute to pain [22,[26][27][28][29][30]] though it is not always possible to directly attribute pain to a specific peripheral structure through diagnostic means in individual cases; hence 'non-specific' is offered as a label in up to 85% of cases [31]. In light of this Lee and Vleeming [32] have introduced an integrated multifactorial model of function in relation to the pelvic girdle which has been adapted here to focus on the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%